Tai Chi for improving cardiopulmonary function and quality of life in patients with chronic obstructive pulmonary disease: a systematic review and meta-analysis. (August 2016) - Guo, Jia-Bao; Chen, Bing-Lin; Lu, Yue-Mei; Zhang, Wen-Yi; Zhu, Zhao-Jin; Yang, Yu-Jie; Zhu, Yi
Objective: To examine the effect of Tai Chi on cardiopulmonary function and quality of life in chronic obstructive pulmonary disease. Data sources: Cochrane Library, PUBMED, EMBASE, China Biology Medicine disc, China National Knowledge Infrastructure, and Wanfang database. Methods: Articles on randomized controlled trials comparing Tai Chi with other treatments or no treatment were identified. A random-effects model was used to calculate the pooled mean difference (MD) with 95% confidence interval (CI). Results: Fifteen articles involving 1354 participants were included. Compared with the control group, Tai Chi was more effective in improving exercise capacity on 6-minute walking distance (short term: MD = 16.02, 95% CI 2.86 to 29.17; mid term: MD = 30.90, 95% CI 6.88 to 54.93; long term: MD = 24.63, 95% CI 2.30 to 46.95), as well as pulmonary functions on forced expiratory volume in the first second (mid term: MD = 0.10; 95% CI 0.01 to 0.19), and forced vital capacity (mid term: MD = 0.20; 95% CI 0.04 to 0.36). Concerning quality of life, we found Tai Chi was better than the control group for the Chronic Respiratory Disease Questionnaire dyspnoea score (short term: MD = 0.90; 95% CI 0.51 to 1.29), fatigue score (short term: MD = 0.75; 95% CI 0.42 to 1.09), and total score (short term: MD = 1.92; 95% CI 0.54 to 3.31). Conclusions: Tai Chi may improve exercise capacity in the short, mid, and long terms. However, no significant long term differences in pulmonary function and quality of life were observed for patients with chronic obstructive pulmonary disease.